Robber Barons Rising: The Potential for Resource Conflict in Ghazni, Afghanistan. Issue 1 (18th February 2014) - Dearing, Matthew P.; Braden, Cynthia
Security and governance in Ghazni Province, Afghanistan are threatened by resource conflict dynamics: groups focus on exploiting lootable resources in the short term while weak institutions and conflict persist. Elements within the Afghan government and insurgent organizations alike expand their power and influence in this manner. Understanding how criminal organizations operate within the regional political economy is essential to reducing the leverage these networks, associated criminal syndicates, and corrupt government officials have on the community. We proffer three hypotheses for development and stability practitioners to monitor as transition approaches in 2014, as well as recommendations for mitigating the onset of resource conflict in Ghazni as the province experiences a downgrade in foreign security forces. Adopting effective, anti-insurgency policies will be fundamental to mitigating the malicious effects on the population and providing incentives for peace, rather than continuing conflict.